2018
DOI: 10.1346/ccmn.2018.064118
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Phosphate by Ivory Coast Shale in a Homogeneous Reactor and Under Hydrodynamic Conditions: Influence of Soluble Species

Abstract: Developing low cost and effective phosphate adsorbents is crucial to prevent eutrophication of natural waters. Here, phosphate removal by a natural and abundant shale from the Ivory Coast was investigated in both batch and column experiments with special attention devoted to understand the adsorption process. Batch experiments were carried out to assess the influence of initial phosphate concentration, sorbent dosage, contact time, and pH on phosphate removal. The phosphate removal efficiency increased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Shales of a larger fraction size also offer poorer efficiency in removing phosphorus due to their lower surface area and higher hydraulic conductivity than smaller material particles [23,24]. Likewise, recent column studies confirmed the maximum sorption capacities for material of 0.06 and 0.23 g P/kg, where the initial mg P/L concentrations were 5 and 25, respectively [25]. Further, the amount of porosity (the ratio of the volume of voids inside the material to the volume of the whole body) did not affect the sorption capacity of shale.…”
Section: Materials With a Pronounced Al/fe Sorption Groupmentioning
confidence: 89%
“…Shales of a larger fraction size also offer poorer efficiency in removing phosphorus due to their lower surface area and higher hydraulic conductivity than smaller material particles [23,24]. Likewise, recent column studies confirmed the maximum sorption capacities for material of 0.06 and 0.23 g P/kg, where the initial mg P/L concentrations were 5 and 25, respectively [25]. Further, the amount of porosity (the ratio of the volume of voids inside the material to the volume of the whole body) did not affect the sorption capacity of shale.…”
Section: Materials With a Pronounced Al/fe Sorption Groupmentioning
confidence: 89%
“…For example, Jain et al [5] adopted montmorillonite (Mt) to prepare Mt-based alginate beads as a delivery vehicle for oral administration of drugs which can effectively reduce the multiple dosing frequency. Besides, the prepared sustained release system usually showed pH-sensitivity as the universal characteristic of clay minerals [19] which was beneficial to the pest control in agriculture [20][21][22]. And the addition of montmorillonite to formulation was found to have a profound inhibitory effect on the release of pesticide reported by previous research [23].…”
Section: Introductionmentioning
confidence: 84%
“…aluminum oxide (17.5%) and iron oxide (10.2%). There is also a minority presence of magnesium oxide (2.1%) manganese oxide (0.6%) and calcium oxide (0.4%) as shown Table 1 (Kpannieu et al, 2018).…”
Section: Physico-chemical Characteristics Of the Substrate Materials ...mentioning
confidence: 99%
“…The uniformity of the particle-size distribution (the uniformity coefficient) was calculated as the ratio between d 60 and d 10 ; according to the literature, materials of 0.2 -1 mm effective size and uniformity coefficient less than 3 are appropriate for substrates of constructed wetlands (Knowles et al, 2011;Mallet et al, 2013). The corresponding values of shale presented in Table 1 satisfy the above-mentioned requirements (Kpannieu et al, 2018). Porosities were determined from the amount of water needed to saturate a known volume of shale and the bulk density of the shale (g•cm −3 ) were based on the ratio between the dry weight and the bulk volume of the sands.…”
Section: Physico-chemical Characteristics Of the Substrate Materials ...mentioning
confidence: 99%